Espacio publico y espacio de los medios: la agenda y las elecciones mexicanas - Escudero Chauvel, Lucrecia (CIC. Cuadernos de Información y Comunicación, 2009)
This text, in a methodological style, analyses the influence that the polítical praxis of the candidates in presidential Mexican election of 2006 have had in the main Mexican newspapers, in order to settle an hypothesis about the functioning of public space and the relationships of power established by media and politicians in the dominance of the public agenda. This is a particularly privileged field to observe the articulation of media, polítical agents and civil society in the structuring of public space, in such an important moment of the democratic life of a country such as the electoral campaign. There is a tension and a bargaining process permanent between the logics of the agents and their strategic rationality, and the logic of the media and their visibilities system, as there is also an intrinsic tension between the polítical discourse of the candidates and their receptors.
Keywords: Presidential campaign; Mexico; Press; Media; Public space; Polítical agents; Society